Pengaruh Cara Aplikasi Minyak Suling Melaleuca bracteata dan Metil Eugenol terhadap Daya Pikat Lalat Buah Bactrocera dorsalis - Agus Kardinan; Momo Iskandar; Ellyda Abas Wikardi (Universitas Gadjah Mada, 1998)
Research has been conducted at farmer’s fruit garden in Cilebut area, Bogor during 1997–1998. The objective is to know the effect of some application techniques of oil distilled from Melaleuca bracteata leaves on trapping fruit fly. Research consisted of three activities, those were the effect of some techniques of application on trapping fruit flies (I) weekly, (2) in two weeks and (3) the effects of some concentrations of methyl eugenol (ME) on trapping fruit fly. All treatments were hung at the fruit trees as high as 1.5 m. Observations were done in the number and gender of fruit flies trapped weekly and two-weekly. Result revealed that melaleuca distilled oil can be applied either by dropping into water or into cotton ball. Melaleuca leaves distilled oil should be applied once in two weeks, since its effectiveness lasted for two weeks only. The minimum concentration of methyl eugenol which could fruit flies effectively was 57%.